Isolation of two new Dehalococcoides mccartyi strains with dissimilar dechlorination functions and their characterization by comparative genomics via microarray analysis. (11th March 2013) - Lee, Patrick K. H.; Cheng, Dan; West, Kimberlee A.; Alvarez‐Cohen, Lisa; He, Jianzhong
Summary Microbial reductive dechlorination of trichloroethene (TCE) in groundwater often results in the accumulation of dichloroethenes (DCEs). Dehalococcoides mccartyi (Dhc) are the only known bacteria capable of dechlorination beyond DCE to non‐toxic ethene. In this study, two newly isolated Dhc strains (11a and 11a5) with dissimilar functional abilities are described. Strain 11a reductively dechlorinates TCE, 1, 1‐DCE, cis‐DCE, trans‐DCE, and vinyl chloride (VC) to ethene, while strain 11a5 dechlorinates TCE and all three DCE isomers only to VC. Each of these dechlorination reactions are coupled to growth by these strains. The VC dechlorination rate of strain 11a occurs at a rate of 258 nmol per min per mg of protein, about two times faster than previously reported stains. Strain 11a possesses the vcrA gene while strain 11a5 contains the tceA gene. Strains 11a and 11a5 share 100% 16S rRNA gene sequence identity with previously sequenced Dhc strains BAV1 and CBDB1, placing it within the Pinellas subgroup, and 85.4% and 89.5% of all genes present in the CBDB1 and BAV1 genomes were detected in strains 11a and 11a5, respectively, using a custom‐designed microarray targeting four sequenced Dhc strains. Genes that were not detected in strains 11a and 11a5 are mostly within the high plasticity regions or integrated elements of the sequenced strains. This study reports the functional description and comparative genomics of two additional Dhc isolates and provides evidence that the observed functional incongruence between the activity and core genome phylogenies of Dhc strains is likely driven by the horizontal transfer of key reductive dehalogenase‐encoding genes.